SISTEM PENDUKUNG KEPUTUSAN PENERIMA BANTUAN PROGRAM KELUARGA HARAPAN (PKH) MENGGUNAKAN METODE TECHNIQUE FOR ORDER OF PREFERENCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) - Raphita Sagala, Jijon; Simangunsong, Agustina (Riau Journal Of Computer Science, 2020)
The poverty that hit Indonesian people became a problem faced by the government, so to overcome poverty since 2007 the Government of Indonesia has implemented the Program Keluarga Harapan (PKH). This Social Protection Program has proven to be quite successful in reducing poverty in Indonesia. In choosing residents in PKH recipients, problems often occur because the data used by PKH from BPS are not up to date, where the data used to determine the PKH recipients in 2019 used data in 2014 which caused new poor families not to receive the Program Keluarga Harapan (PKH). The problem that often occurs is that manual selection requires a lot of time and the selection of participants can be influenced by the objective assessment of PKH companions, the criteria of citizens surveyed are not in accordance with government regulations, and the government determines the number of PKH recipient quotas, so that there are still communities did not accept PKH. To deal with the problem a decision support system is needed to help the Village Government determine PKH recipient residents, one of the decision support system methods is the TOPSIS method. The system is built based on Desktop Applications which can improve data quality and effectiveness of PKH participant selection so that PKH assistance can be received right on target